THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT THE CELIKAH COMMUNITY HEALTH CENTER, KAYU AGUNG DISTRICT, OGAN KOMERING ILIR REGENCY - Manurung, Henson Enjein (Jurnal Manajemen, 2024)
Leadership style is one component that influences employee performance. Performance is the result of work carried out by individuals or groups of people in an organization in accordance with their authority and responsibility to achieve organizational goals legally, without violating the law, and in accordance with morals and ethics. This research aims to assess the influence of leadership style on employee performance. The objects of this research were employees at the Celikah Community Health Center, Kayu Agung, Ogan Komering Ilir Regency. The approach used in this research is an associative approach with causal relationships and aims to prove. The population in this study were all employees of the Celikah Community Health Center, Kayu Agung, with a sample size of 95 people. This research uses SPSS 26 as a calculation tool.